A pilot study of the effects of high‐frequency repetitive transcranial magnetic stimulation on dysphagia in the elderly. Issue 5 (28th January 2019) - Park, Jin‐Woo; Kim, Hyojun; Park, Taejune; Yeo, Jeong‐Seok; Hong, Ho‐Jin; Oh, Jin‐Young
Abstract: Background: Swallowing difficulty is common in the geriatric population and is associated with brain activity alteration with advancing age. Repetitive transcranial magnetic stimulation (rTMS) is a noninvasive approach to stimulate cortical neurons and can produce changes in cortical excitability. The objective of this study is to determine whether rTMS induces positive changes in the cortical areas and facilitates swallowing function in the elderly diagnosed with dysphagia. Methods: Eight right‐handed elderly dysphagia patients without any neurologic deficits received 5 Hz rTMS to a pharyngeal motor hot spot in the right hemisphere for 10 minutes every weekday for 2 weeks. The intensity of the stimulation was set at 90% of the thenar motor threshold of the same hemisphere. They were all subjected to 18F‐labeled fluorodeoxyglucose‐PET scans at swallowing before and after rTMS. Differences between each patient's active image and control images on a voxel‐by‐voxel basis were examined to find significant increases in metabolism using statistical parametric mapping software. Videofluoroscopic swallowing study was also conducted before and after magnetic stimulation intervention. Penetration‐aspiration scale (PAS) and videofluoroscopic dysphagia scale (VDS) were compared to evaluate swallowing function. Key Results: After 2 weeks of rTMS intervention, the VDS score was significantly reduced (from 43.6 ± 10.3 to 27.2 ± 14.5: P  < 0.05), and especially pharyngeal motor function was improved. Activation was significantly increased in the bilateral primary motor cortex, premotor cortex, and right prefrontal cortex, which showed asymmetry. Conclusions and Inferences: High‐frequency rTMS positively affected the activation in cortices and swallowing function in elderly patients with dysphagia. Abstract : High‐frequency rTMS over the pharyngeal motor cortex improved swallowing function and asymmetrically increased brain activity in cortical area related swallowing function in elderly dysphagia patients. The findings suggested a different pattern compared with normal aging presbyphagia.